2019
DOI: 10.1186/s12943-019-1095-y
|View full text |Cite
|
Sign up to set email alerts
|

circGSK3β promotes metastasis in esophageal squamous cell carcinoma by augmenting β-catenin signaling

Abstract: Background: Circular RNAs (circRNAs), a novel class of noncoding RNAs, have recently drawn much attention in the pathogenesis of human cancers. However, the role of circRNAs in esophageal squamous cell carcinoma (ESCC) remains unclear. In this study, we aimed to identify novel circRNAs that regulate ESCC progression and explored their regulatory mechanisms and clinical significance in ESCC.Methods: Differentially expressed circRNAs between ESCC and paired adjacent normal tissues were identified using microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 37 publications
0
117
0
Order By: Relevance
“…Circular RNAs (circRNAs) are a class of novel endogenous non-coding RNAs (ncRNAs) with a covalently closed continuous loop, and they are generated by the selective cleavage of premature RNAs [3]. The loop structure produced by linking 5' and 3' end renders circRNAs resistant to exonucleases and more stable than their corresponding linear transcripts [4]. In 2011, Salmena L et al proposed a competing endogenous RNA (ceRNA) hypothesis, in which ncRNAs could positively regulate mRNA expression through competitively binding to shared microRNAs (miRNAs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of novel endogenous non-coding RNAs (ncRNAs) with a covalently closed continuous loop, and they are generated by the selective cleavage of premature RNAs [3]. The loop structure produced by linking 5' and 3' end renders circRNAs resistant to exonucleases and more stable than their corresponding linear transcripts [4]. In 2011, Salmena L et al proposed a competing endogenous RNA (ceRNA) hypothesis, in which ncRNAs could positively regulate mRNA expression through competitively binding to shared microRNAs (miRNAs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Leading to poor prognosis in ESCC, upregulated circRNA_100876 expression can accelerate cell proliferation and metastasis [ 32 ], while the upregulation of circRNA_100873 is associated with increased lymphatic metastasis in ESCC [ 33 ]. A further study reported that circGSK3 overexpression enhances multiple metastasis and invasion of the tumor [ 34 ]. The underlying mechanisms of circRNAs and miRNAs in ESCC patient survival remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further evaluate the predictive value of plasma circGSK3β level for postoperative clinical improvement and whether it can predict the recurrence and metastasis of ESCC, further research were carried out and the results showed that the level of circGSK3β in patients with recurrence/metastasis was significantly higher than that in patients without recurrence/metastasis 10 months after operation. It is suggested that the level of plasma circGSK3β may be a valuable predictor of recurrence/ metastasis of EC [37]. Following results showed that the expressions of circ_0000654 [38], circPVT1 [39], circ_0006168 [40], circ_0004370 [41], circ-TTC17 [42], circ_0067934 [43], circ_0006948 [44], circ_0030018 [45], circ_100876 [46], circ-DLG1 [47] and circ-SLC7A5 [48] were up-regulated in EC and related to the poor prognosis of EC.…”
Section: Circrnas As Biomarkers In Ecmentioning
confidence: 97%
“…Compared with paracancerous tissues, the expressions of hsa_circ_0067934, circFNDC3B, circ-TTC17, hsa_circ_0006168, circPVT1 and hsa_circ_100873 were significantly up-regulated in EC tissues [ 39 , 40 , 42 , 43 , 56 , 57 ]. So far, cir-ITCH, circ-PRKCI, circRAD23B, cZNF292, circ-Foxo3, circGSK3 β, circLARP4 and hsa_circ_0004771 have been shown to regulate the proliferation and apoptosis of EC cells through different signal pathways [ 35 , 37 , 50 , 58 62 ]. In a word, different results suggest that circRNAs may promote or inhibit development of EC through different mechanisms (Fig.…”
Section: Role and Significance Of Circrnas In Ecmentioning
confidence: 99%